Comprehensive Healthcare Simulation: Neurosurgery (Comprehensive Healthcare Simulation, 2018)
This book is a practical guide for the use of simulation in neurosurgery, with chapters covering high fidelity simulation, animal models simulation, cadaveric simulation, and virtual reality simulation. Readers are introduced to the different simulation modalities and technologies and are guided on the use of simulation for a variety of learners, including medical students, residents, practicing pediatricians, and health-related professionals. Comprehensive Healthcare Simulation: Neurosurgery is written and edited by leaders in the field and includes dozens of high-quality color surgical illustrations and photographs as well as videos. This book is part of the Comprehensive Healthcare Simulation Series which provides focused volumes on the use of simulation in a single specialty or on a specific simulation topic, and emphasizing practical considerations and guidance.